DEVELOPING SCRATCH GAME INTEGRATED INTERACTIVE E-LKPD TO MEASURE JUNIOR HIGH STUDENTS' MATHEMATICS COMPREHENSION - Sri Malisa; Nurul Anriani; Anwar Mutaqin (Universitas Muhammadiyah Metro, 2026)
Students' mathematical conceptual understanding at the junior high school level remains relatively low, while learning media specifically designed to assess this ability are still limited. In addition, mathematics learning is often less varied, passive, and lacks the integration of technology-based educational games. This study aimed to develop an interactive Electronic Student Worksheet (E-LKPD) integrated with Scratch games to assess and enhance students' mathematical conceptual understanding. The study employed a Research and Development (R&D) approach using the Borg and Gall development model, which consists of nine stages: preliminary study, research planning, product design development, preliminary field testing, initial product revision, main field testing, further product revision, operational field testing, and final product revision. The research was conducted at SMPN 18 Serang City, involving 40 eighth-grade students selected through purposive sampling. Data were collected using expert validation questionnaires, student response questionnaires, and a mathematical conceptual understanding test. The results indicated that the developed E-LKPD achieved a validity score of 83% from material experts and 85% from media experts, both categorized as highly valid. The practicality test based on students' responses yielded a score of 76%, indicating that the product was practical. Furthermore, the effectiveness test resulted in a score of 83%, categorized as effective. These findings demonstrate that the Scratch-integrated interactive E-LKPD meets the criteria of validity, practicality, and effectiveness, making it suitable for use as both a learning medium and an assessment tool for measuring junior high school students' mathematical conceptual understanding. Kemampuan pemahaman konsep matematika siswa SMP masih tergolong rendah, sementara media pembelajaran yang secara khusus digunakan untuk mengukur kemampuan tersebut belum banyak tersedia. Selain itu, pembelajaran matematika cenderung kurang bervariasi, bersifat pasif, dan belum memanfaatkan teknologi yang terintegrasi dengan permainan edukatif. Penelitian ini bertujuan mengembangkan E-LKPD interaktif yang terintegrasi game Scratch untuk mengukur sekaligus meningkatkan kemampuan pemahaman konsep matematika siswa SMP. Penelitian menggunakan metode Research and Development (R&D) dengan model Borg & Gall yang meliputi sembilan tahap, yaitu studi pendahuluan, perencanaan penelitian, pengembangan desain produk, uji coba lapangan awal, revisi awal produk, uji coba lapangan utama, revisi lanjutan produk, uji coba lapangan operasional, dan revisi akhir produk. Penelitian dilaksanakan di SMPN 18 Kota Serang dengan sampel sebanyak 40 siswa kelas VIII yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui angket validasi ahli, angket respons siswa, dan tes kemampuan pemahaman konsep matematika. Hasil penelitian menunjukkan bahwa E-LKPD yang dikembangkan memperoleh tingkat validitas sebesar 83% dari ahli materi dan 85% dari ahli media dengan kategori sangat valid. Hasil uji kepraktisan berdasarkan respons siswa memperoleh persentase sebesar 76% dengan kategori praktis. Adapun hasil uji keefektifan menunjukkan persentase sebesar 83% dengan kategori efektif. Temuan ini menunjukkan bahwa E-LKPD interaktif terintegrasi game Scratch memenuhi kriteria valid, praktis, dan efektif sehingga layak digunakan sebagai media pembelajaran sekaligus instrumen untuk mengukur kemampuan pemahaman konsep matematika siswa SMP.